Biocidal Agents Used for Disinfection Can Enhance Antibiotic Resistance in Gram-Negative Species - Günter Kampf (MDPI AG, 2018)
Biocidal agents used for disinfection are usually not suspected to enhance cross-resistance to antibiotics. The aim of this review was therefore to evaluate the effect of 13 biocidal agents at sublethal concentrations on antibiotic resistance in Gram-negative species. A medline search was performed for each biocidal agent on antibiotic tolerance, antibiotic resistance, horizontal gene transfer, and efflux pump. In cells adapted to benzalkonium chloride a new resistance was most frequently found to ampicillin (eight species), cefotaxime (six species), and sulfamethoxazole (three species), some of them with relevance for healthcare-associated infections such as Enterobacter cloacae or Escherichia coli. With chlorhexidine a new resistance was often found to ceftazidime, sulfamethoxazole and imipenem (eight species each) as well as cefotaxime and tetracycline (seven species each). Cross-resistance to antibiotics was also found with triclosan, octenidine, sodium hypochlorite, and didecyldimethylammonium chloride. No cross-resistance to antibiotics has been described after low level exposure to ethanol, propanol, peracetic acid, polyhexanide, povidone iodine, glutaraldehyde, and hydrogen peroxide. Taking into account that some biocidal agents used in disinfectants have no health benefit (e.g., in alcohol-based hand rubs) but may cause antibiotic resistance it is obvious to prefer products without them.